PENGARUH SELF CONGRUITY MEREK TERHADAP LOYALITAS MEREK DENGAN ASOSIASI MEREK DAN PERSEPSI KUALITAS SEBAGAI VARIABEL MEDIASI PADA PELANGGAN TOKO SEPATU BATA DI BANDA ACEH - Novi Restia, Syarifah Evi Zuhra (Departemen Manajemen, 2018)
This study aims to determine the effect of brand congruity on brand loyalty with brand association and quality perception as mediator. The empirical study was conducted on brick shoe store customer in Banda Aceh using questionnaire as research instrument, which the sample in this research is 136 respondents. Non Probability Sampling is used as sampling technique with Purposive Sampling method. The Hierarchical Linear Modeling (HLM) method is used as a data analysis method using the IBM SPSS 25 software. The results of this study indicate that the brand self-congruity has a significant effect on brand loyalty In addition, the results obtained that the variables of brand association and quality perception mediate partially influence Self brand congruity on brand loyalty. The better the self-owned brand congruity, the better the brand association and the perception of quality, the higher the brand loyalty the customer has. Keywords: Self Congruity, Brand Loyalty, Brand Association, Perceived quality.